Self-Management in Daily Life with Psoriasis: An Integrative Review of Patient Needs for Structured Education - Gitte Susanne Rasmussen; Helle Terkildsen Maindal; Kirsten Lomborg (Nursing Research and Practice)
The aim of this integrative review is to identify and discuss patient needs for education to support self-management in daily life with psoriasis. As psoriasis increasingly gains recognition as a serious chronic autoimmune skin disease with long-term impairment on the life course, and not mainly a cosmetic problem, nurses are highly challenged to develop efficient education to support patient self-management. The paper includes five stages: (1) problem identification, (2) literature search, (3) data evaluation, (4) data analysis and synthesis, and (5) presentation, based on theoretic scaffolding around the concept “need.” Nineteen of 164 original papers within nursing, medicine and psychology, and reflecting patient perspective were included. To capture the patients’ cultural understanding of the implications of the disease and care, we developed an interlevel model indicating that self-experienced burden of disease and its visibility, personal conditions such as illness perception, and the patient’s age at onset time are high-impact factors that should be addressed in future structured patient education programmes. The research on patient needs has hitherto focused on adults, but the problems and vulnerability associated with having a chronic and visible disease during adolescence must be acknowledged, and patient education initiatives designed for this young group are recommended.